Pengaruh Peran Perempuan dalam Dewan, Kinerja ESG, dan Penghindaran Pajak - Elfina Astrella Sambuaga; Donia Felicia (Society, 2024)
This research examines the impact of board gender diversity on tax avoidance, with ESG performance as an intervening variable. Using 87 non-financial companies listed on the Indonesia Stock Exchange (IDX) with ESG scores from Thomson-Reuters ASSET4 during the 2017-2019 period, the study reveals that board gender diversity significantly influences tax avoidance, indicating that diversity does not improve tax compliance. The male-dominated boards in Indonesia limit the effectiveness of monitoring corporate activities, including tax avoidance. Additionally, gender diversity negatively affects ESG performance, suggesting that the small number of women on boards diminishes efforts to enhance sustainability. ESG performance does not mediate the relationship between gender diversity and tax avoidance, though it can reduce tax avoidance when transparency in ESG reporting is increased. Limitations include a small sample size and data restricted to the 2017-2019. Future studies could explore alternative tax avoidance measures and other corporate governance factors.